2020
DOI: 10.18332/tid/118232
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation is related to change in metabolic syndrome onset: A rural cohort study

Abstract: INTRODUCTION Relatively few, mainly cross-sectional, studies have examined the relationship between smoking cessation and metabolic syndrome (MetS). In particular, information on smoking cessation after MetS is limited. This study aimed to investigate the probability of smoking cessation after the onset of MetS. METHODS In this study we used cohort data from a rural area of Korea and extracted the data of 1054 smokers who were identifiable at baseline and were followed up. Of these, 1041 individuals were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The characteristics of the eligible studies are summarized in Table 1. Of the 24 articles included in the study, 13 were cross-sectional studies, [10,17–22,25,27–29,31,36] 10 were cohort studies, [3,19,23,24,26,32,33,35,37,38] 1 was a randomized controlled trial (RCT), [30] and 1 was a case-control study. [34] Regarding region, 15 studies in Asia, 4 in Europe, 3 in Middle East, and 2 in America were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the eligible studies are summarized in Table 1. Of the 24 articles included in the study, 13 were cross-sectional studies, [10,17–22,25,27–29,31,36] 10 were cohort studies, [3,19,23,24,26,32,33,35,37,38] 1 was a randomized controlled trial (RCT), [30] and 1 was a case-control study. [34] Regarding region, 15 studies in Asia, 4 in Europe, 3 in Middle East, and 2 in America were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in significant heterogeneity among studies. Third, some studies did not consider factors such as weight change [24,33,38] or the amount of smoking [20] before cessation, which has had an impact on the analysis Furthermore, only 41% of the studies have reported the duration of smoking cessation, [3,10,[19][20][21]23,24,26,30,32,35,38] and the varying timeframes across different studies make it challenging to integrate the findings. Of the 5 studies involving women, [17,18,22,23,34] available data on the prevalence of MS based on smoking status are scarce, thus making it difficult to include it in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation